2009
DOI: 10.1080/10926750903313278
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Gay/Lesbian and Heterosexual Adoption

Abstract: Many experts in the helping

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
1
8

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 38 publications
0
34
1
8
Order By: Relevance
“…This legal change, however, has not been followed by practical opportunities for same-sex couples, thus lesbian couples generally have children through birth giving. Joint adoption is a well-established path to parenthood for lesbians in countries like the United Kingdom, the United States and Canada (Ausbrooks & Russel, 2011;Averett, Nalavany & Ryan, 2009;Brown et al, 2009;Farr & Patterson, 2009;Hicks, 2011;Kinkler & Goldberg, 2011;Ross et al, 2008;Woodford et al, 2010), again in contrast to results from the present Swedish study.…”
Section: Chapter VI Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…This legal change, however, has not been followed by practical opportunities for same-sex couples, thus lesbian couples generally have children through birth giving. Joint adoption is a well-established path to parenthood for lesbians in countries like the United Kingdom, the United States and Canada (Ausbrooks & Russel, 2011;Averett, Nalavany & Ryan, 2009;Brown et al, 2009;Farr & Patterson, 2009;Hicks, 2011;Kinkler & Goldberg, 2011;Ross et al, 2008;Woodford et al, 2010), again in contrast to results from the present Swedish study.…”
Section: Chapter VI Discussioncontrasting
confidence: 56%
“…Once the decision to parent is grounded, the prospective mother(s) might consider several routs to parenthood depending on social conventions, personal preferences and values, legal access and economic resources etcetera (Mezey, 2008; see also Ryan-Flood, 2009;Wojnar & Katzenmeyer, 2014). One route to parenthood is to apply for adoption or to have foster children (Ausbrooks & Russel, 2011;Averett, Nalavany, & Ryan, 2009;Brown, Smalling, Groza & Ryan, 2009;Farr & Patterson, 2009;Goldberg, 2009;Goldberg, Downing & Sauck, 2007;Goldberg, Moyer, Kinkler & Richardson, 2012;Goldberg & Smith, 2011;Mallon, 2011;Ross et al, 2008;Ross, Epstein, Anderson, & Eady, 2009;Ryan & Whitlock, 2007;Woodford et al, 2010). Others choose assisted reproduction and may have donor insemination or IVF.…”
Section: Studies On Lesbian Family Life and Practicesmentioning
confidence: 99%
“…Perhaps some combination of the fathers and the adoption authorities they worked with believed that fathers are better suited to raise boys. Likewise, but to a lesser degree, Averett, Nalavany, and Ryan's (2009) study reported a 58% to 42% ratio of boys to girls in gay male-parented adoptive families while Goldberg, Kashy, and Smith's (2012) study reported a 45% to 55% ratio of boys to girls in lesbian parented families, 56% to 44% in gay male-parented families, and 48% to 52% in heterosexual families. None of these latter examples approach statistical significance, but the direction of the data remains the same.…”
Section: Disparity In Children's Gendermentioning
confidence: 88%
“…Les enfants adoptés par des pères gays vivent-ils davantage de problèmes que ceux adoptés par des mères lesbiennes ou des parents hétéro-sexuels ? Une étude montre que les problèmes psychologiques d'enfants adoptés par des parents hétérosexuels, des mères lesbiennes ou des pères gays ne dépendaient pas de l'orientation sexuelle des parents (Averett et al, 2009). Plusieurs études menées à partir d'échantillons constitués de parents adoptifs, sans distinguer les mères lesbiennes et les pères gays, à partir d'autoquestionnaires, décrivent un fonctionnement familial positif et des enfants présentant un ajustement psychologique positif (Erich et al, 2009 ;Erich et al, 2005 ;Leung et al, 2005).…”
Section: Travaux Anglo-saxonsunclassified